1995
DOI: 10.1002/jez.1402710405
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal organization in clusters of isolated polarized skate hepatocytes: Structural and functional evidence for microtubule‐dependent transcytosis

Abstract: Isolated hepatocytes from the marine vertebrate Raja erinacea (the little skate) retain their structural and functional integrity as clusters of cells formed around a single tubular bile canaliculus, and therefore can be used as a model of polarized hepatocytes in situ. In this study we used confocal and conventional epifluorescence microscopy in conjunction with fluorescent markers and immunocytochemistry to examine the structure and function of the cytoskeleton in these cells. Actin filaments in the hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Thus, Can 10 and Can 9 are the first models with functional highly developed BC reminiscent of those found in vivo. Developed functional BC are not often observed in hepatocyte primary cultures, except for hepatocytes from the marine vertebrate Raja erinacea (Henson et al 1995). However, in this last model, as in hepatocyte couplets, BC are preserved but never newly formed.…”
Section: Properties and Usefulness Of The Polarized Modelsmentioning
confidence: 98%
“…Thus, Can 10 and Can 9 are the first models with functional highly developed BC reminiscent of those found in vivo. Developed functional BC are not often observed in hepatocyte primary cultures, except for hepatocytes from the marine vertebrate Raja erinacea (Henson et al 1995). However, in this last model, as in hepatocyte couplets, BC are preserved but never newly formed.…”
Section: Properties and Usefulness Of The Polarized Modelsmentioning
confidence: 98%
“…With Jim Boyer, Yale Medical School, New Haven, CT, David also studied isolated hepatocytes from the marine vertebrate Raja erinacea (little skate; [52]). Using confocal fluorescence microscopy, David and colleagues elucidated the cellular organization of actin filaments and observed that nocodazole disrupted transcytosis of a fluorescent bile salt derivative into canalicular lumens.…”
Section: The 1990s To the Millennium: Head Of The Intracellular Regulmentioning
confidence: 99%
“…Leucoraja erinacea has been used for a number of years in studies of liver function (Barnes et al , 2005). The cells are interesting because, among other phenomena, they do not synthesize albumin, they produce bile alcohols instead of bile acids and they are a useful system for comparative studies on evolutionarily conservation of vertebrate hepatocyte structures (Henson et al , 1995). In addition to studies with perfused liver and molecular studies of genes cloned from the liver cells, a relatively simple culture system has been devised to allow studies of isolated L. erinacea hepatocytes (Smith et al , 1987).…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%
“…The cultures also have been used to characterize chloride and manganese uptake and release (Davis‐Amaral et al , 1996, 1997; Madejczyk et al , 2009). Ultrastructural and functional studies in vitro have shown that the microtubule cytoskeleton is involved in an essential way in transcytosis, endocytosis and bile excretory function (Henson et al , 1995; Miller et al , 1996).…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%